2020
DOI: 10.1253/circj.cj-20-0257
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural Predictors of New-Onset Conduction Abnormalities After Transcatheter Aortic Valve Replacement

Abstract: Pre-existing right bundle branch block (RBBB), firstdegree AVB, self-expandable valves, intraoperative AVB, implantation depth (ID), and the length of the membranous septum (MS) have been identified as predictors of CAs. 10-14 However, the majority of studies have been restricted to earlier-generation prostheses and the definitions of CAs have been limited to new PPM implantation. The present study was therefore designed to delineate the predictive factors of new-onset LBBB and new PPM implantation after TAVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…After excluding duplicates and noneligible studies, 18 studies 4,6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] met our eligibility criteria (Supporting Information: Figure 1). All the studies were nonrandomized and observational, while four studies were multicentric and five studies included matched populations (Table 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…After excluding duplicates and noneligible studies, 18 studies 4,6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] met our eligibility criteria (Supporting Information: Figure 1). All the studies were nonrandomized and observational, while four studies were multicentric and five studies included matched populations (Table 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Importantly, new‐onset LBBB and PPI were associated with mortality and HF hospitalization. Our prior study consistently showed that new‐onset LBBB and/or PPI led to a two‐fold higher major adverse clinical events at 3 year follow‐up 86 . In a recent meta‐analysis of 50 282 TAVI patients, 7232 patients underwent PPI after TAVI and had an increased mortality rate [hazard ratio: 1.21 (95% confidence interval: 1.14–1.28); P < 0.001] and HF rehospitalization [hazard ratio: 1.30 (95% confidence interval: 1.17–1.45); P < 0.001] 87 .…”
Section: Complications Associated With Heart Failure Hospitalization ...mentioning
confidence: 60%
“…The most frequent complications after TAVI are conduction disturbance such as high-degree atrioventricular block leading to new-onset left bundle branch block (LBBB) and permanent pacemaker implantation (PPI). 85,86 A large meta-analysis of 30 studies demonstrated that the incidence of new-onset LBBB ranged from 10.5% to 52.3%, whereas PPI at discharge ranged from 5.9% to 32.0%. 85 Importantly, new-onset LBBB and PPI were associated with mortality and HF hospitalization.…”
Section: Conduction Disturbance and Permanent Pacemaker Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several studies demonstrated that the MS length and implantation depth were predictors of conduction disturbance in patients treated with TAVI procedures. [19][20][21] When the guiding sutures are used below the annulus 1 mm (new guiding suture technique), the maximum implantation depth will be 4.9 mm (S), 5.2 mm (M), 5.5 mm (L), and 5.8 mm (XL). In this study, only 1 patient (2.5%) required PPI, although no significant association was observed between the new guiding suture technique and PPI.…”
Section: Advance Publication Early Clinical Outcomes Of Perceval Valve In Koreamentioning
confidence: 99%